PP68 Optimal central obesity measurement site for assessing cardiometabolic and type 2 diabetes risk in middle-aged adults. (2nd September 2014) - Millar, SR; Perry, IJ; Van den Broeck, J; Phillips, CM
Abstract : Background: Despite recommendations that central obesity assessment should be employed as a marker of cardiometabolic health, no consensus exists regarding measurement protocol. This study examined a range of anthropometric variables and their relationships with cardiometabolic features and type 2 diabetes in order to ascertain whether measurement site influences discriminatory accuracy. In particular, we compared waist circumference (WC) measured at two sites: (1) below the lowest rib (WC rib) and (2) between the lowest rib and iliac crest (WC midway), which has been recommended by the World Health Organisation (WHO) and International Diabetes Federation (IDF). Methods: This was a cross-sectional study involving a random sample of 2, 002 men and women aged 50–69 years. Metabolic profiles and WC, hip circumference, pelvic width and body mass index (BMI) were determined in study participants. Correlation, logistic regression and covariate-adjusted area under the receiver operating characteristic curve analyses were used to evaluate obesity measurement associations and discrimination for metabolic risk phenotypes and type 2 diabetes. Results: Rib measurements displayed, without exception, the strongest associations for non-optimal lipid profiles, high blood pressure, insulin resistance, impaired fasting glucose, a clustering of metabolic risk features and type 2 diabetes, in both genders. Rib-derived indices improved discrimination for type 2 diabetes by 3–7% compared to BMI and 2–6% compared to WC midway (in men) and 5–7% compared to BMI and 4–6% compared to WC midway (in women). Conclusion: WC rib is easier to measure and our data suggest that it is a better method for determining obesity-related cardiometabolic risk than WC midway. Rib measurements may provide a more convenient and precise method for discriminating cardiometabolic outcomes. The clinical utility of rib-derived indices as potentially more accurate predictors of type 2 diabetes, compared to WHO and IDF-recommended WC midway measurement or BMI, requires further investigation.